Integrated omics for increasing plant production and health‐related nutrition under extreme conditions: The Indonesia perspective - Enny Sudarmonowati; Alfia Aini Annur Azizi; Aviv Andriani; Sri Koerniati; Eny Ida Riyanti; Edy Listanto; Carla Frieda Pantouw; Bernadetta Rina Hastilestari; Decintya Jaya Maysha (Universitas Gadjah Mada, 2025)
Despite Indonesia being a megadiverse country that provides germplasm for breeding to produce improved future varieties, significant threats are faced related to biodiversity extinction. Such threats, for example habitat degradation and climate change, which lead to extreme conditions, must be addressed as they have contributed to stresses at the molecular level and affect plant production and health‐related nutrition. Integrated omics approaches have been applied to address the problems, as well as to produce varieties with superior traits, which are critical factors in achieving improved plant production and better naturally derived human nutrition. The paper discusses the omics research agenda in Indonesia; Indonesian biodiversity of nutraceutical plants and how omics can increase its production. Besides, current progress of omics application in Indonesia, policies and regulations to enhance integrated omics research are elucidated. By applying these approaches in Indonesia, breeding for better traits to support human needs and improve health quality will be greatly accelerated in the future.